2019
DOI: 10.2135/cropsci2018.09.0537
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Realized Rates of Genetic Gain and Indicators for Breeding Program Assessment

Abstract: R ealized genetic gain is the change in average breeding value of a population over at least one cycle of selection for a particular trait or index of traits. Change in breeding or genetic values of populations over many cycles or years is referred to as genetic trend. When a genetic trend is linear, the rate of genetic gain per year (DG t ) that is realized can be estimated by regressing the average breeding value on year (Eberhart, 1964). Assuming the breeding process remains unchanged and the trait of inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…We believe most applied plant breeders would agree that this criterion is most appropriate. This emphasizes that population improvement may not be the best indicator of a breeding program’s performance, a metric that has also been shown to be biased by environmental trends (Rutkoski 2019).…”
Section: Resultsmentioning
confidence: 99%
“…We believe most applied plant breeders would agree that this criterion is most appropriate. This emphasizes that population improvement may not be the best indicator of a breeding program’s performance, a metric that has also been shown to be biased by environmental trends (Rutkoski 2019).…”
Section: Resultsmentioning
confidence: 99%
“…phenotypic selection in the current study was very much lower than what was reported by Gaynor et al (2017) while for GS we did not observe huge difference in reported genetic gain with their studies. Rate of genetic gain is used to compare an outcome from different breeding schemes that will help in designing a new breeding program (Rutkoski, 2019). Our study showed that the increase in genetic gain that came by adding genomic information at the preliminary selection stage could help a wheat breeder for practical decision making to switch to GS breeding program.…”
Section: Genetic Gainmentioning
confidence: 96%
“…Additionally, yields of major crops including wheat, rice, maize and soybean have stagnated or even collapsed due to harsher climatic conditions in some parts of the world [18][19][20]. Positive trends in genetic gain continue to be achieved in individual breeding programs, but at the expense of eroding large parts of genetic diversity [11,[21][22][23]. Will it, therefore, be possible to increase or even maintain the rate of genetic gain in the coming decades, despite the deteriorating climate conditions?…”
Section: Introductionmentioning
confidence: 99%